Percentage and Risk Factors of Urinary Tract Infections among Pregnant Women attending FANC Visits in Public Secondary Hospitals in Jama’a LGA, Kaduna State - Yaki, Peter Francis; O., Nworuh B.; O., Udujih G.; M., Mato B. D. (Darul Yasin Al Sys, 2025)
Urinary Tract Infections (UTIs) are among the most common infections affecting pregnant women, contributing significantly to maternal and fetal morbidity. In Nigeria, especially in rural areas such as Jama’a Local Government Area (LGA) of Kaduna State, limited data exist on the burden and risk factors associated with UTIs during focused antenatal care (FANC) visits. This study assessed the percentage and risk factors of UTIs among pregnant women attending FANC visits in public secondary hospitals in Jama’a LGA, Kaduna State. A hospital-based cross-sectional descriptive study was conducted among 301 pregnant women. Midstream urine samples were collected and cultured on Cysteine Lactose Electrolyte Deficient (CLED) agar. Socio-demographic and clinical data were obtained through structured questionnaires. Chi-square tests were used to determine associations between demographic variables and UTI occurrence at a 5% significance level. The percentage of UTIs among the study population was 28.6%. Escherichia coli (45.3%) was the most frequently isolated organism, followed by Klebsiella pneumoniae (19.8%) and Staphylococcus aureus (16.3%). Statistically significant risk factors associated with UTI were maternal age ≥35 years (AOR=1.91; p=0.041), parity ≥4 (AOR=2.14; p=0.006), prior history of UTI (AOR=3.42; p<0.001), and poor perineal hygiene practices (AOR=1.78; p=0.027). The study revealed a high percentage of UTIs among pregnant women in Jama’a LGA. Regular screening, targeted interventions for high-risk groups, and improved hygiene education during FANC visits are recommended to reduce the burden of UTIs in pregnancy.